CD2-targeted nanoparticles encapsulating IL-2 induce tolerogenic Tregs and TGF-β-producing NK cells that stabilize Tregs for long-term therapeutic efficacy in immune-mediated disorders - Horwitz, David A.; Kim, Dongin; Kang, Chang; Brion, Katja; Bickerton, Sean; La Cava, Antonio (Frontiers in Immunology, 2025)
T regulatory cells (Tregs) generated in the periphery (pTregs) are initially unstable, but some of them stabilize with time. The stabilization signals, however, are poorly understood. We have previously reported that the treatment of mice with poly(lactic-co-glycolic) acid (PLGA) nanoparticles (NPs) decorated with anti-CD2 antibodies and encapsulating IL-2 and TGF-β induced tolerogenic CD4+ and CD8+ pTregs that protected mice from fatal graft-versus-host disease (GvHD). These NPs also induced TGF-β-producing NK cells. Here we show that initially unstable Tregs are stabilized and maintained by NK-cell derived TGF-β. Blockade of TGF-β signaling or NK cell depletion hindered the induction of Tregs and converted tolerogenic responses into immunogenic responses, leading to an accelerated demise of the mice. IL-2 from the NPs and TGF-β from NP-induced NK cells were sufficient for the maintenance of the Tregs, making the encapsulated TGF-β unnecessary. These results identify a new non-redundant cellular source of TGF-β required for the support of newly induced Tregs. NPs inducing cross-communicating innate and adaptive tolerogenic cells can represent a new cell-targeted approach to induce and maintain long-term immune tolerance in immune-mediated diseases.